Democratic Federalism : The Economics, Politics, and Law of Federal Governance - Inman, Robert P.; Rubinfeld, Daniel L. (Book collections on Project MUSE., 2020)
"Federalism, defined generally as a collection of self-governing regions under a central government, is widely viewed as a sensible choice of polity both for emerging democracies and for established states. But while federal institutions are positively correlated with valued economic, democratic, and justice outcomes, ultimately it is unclear how they are connected and which cause which. In Democratic Federalism, Robert Inman and Daniel Rubinfeld explore how federalism works and propose concrete and proven policy guidance on how federalist policies can be designed and implemented successfully. The authors define federalism according to three parameters: how much federal revenue comes through local governmental bodies, the number of local governmental bodies, and the extent to which these local bodies are represented federally. In applying these parameters to economic concepts and theory, Inman and Rubinfeld explain how federalism works in a way meant to engage scholars in political science and sociology and policymakers drafting regulation in federalist governments. The book offers applicable ideas and comparative case studies on how to assess potential policies and how to actually design federalist institutions from scratch. Both authors have real experience with both, most notably in their work advising the South African government on how to build a federalist democracy. This book will be an essential guide to understanding and applying federalist concepts and principles"--